The impact of land use transition on ecosystem service value in Lixiahe area: Multi-scenario simulation based on Markov-FLUS model - CHEN Xinwei, LI Hongbo, ZHANG Wenbo, GE Xiaoping (Ziyuan Kexue)
[Objective] The Lixiahe area in Jiangsu Province is an important river floodplain network depression in the Huaihe Basin, and it is a typical zone where agriculture, ecology, and urbanization interweave. In the context of ecological civilization construction, simulating the land use transformation in this region under multiple scenarios and its impact on the value of ecosystem services have practical guiding significance. [Methods] Based on the land cover data of 1990, 2005 and 2020, this paper analyzes the characteristics of land use and changes in ecosystem service value. Three scenarios, namely, inertial development, cultivated land protection and ecological priority, are set up, and the Markov-FLUS model is used to simulate the impact of land use change on ecosystem service value. [Results] (1) From 1990 to 2020, the dominant land use type in the study area was cultivated land. The main changes in land use were the reduction of cultivated land and the increase of construction land. The main form of land use type transformation was from cultivated land to wetland or construction land, and the active transformation areas were concentrated in the central and eastern and western boundary areas. (2) The ecosystem service value of the study area in 1990, 2005 and 2020 showed a year-on-year increasing trend, and the spatial pattern was relatively stable. Overall, it presented a distribution feature of “low on the periphery and high in the center”. (3) The Markov-FLUS model has strong applicability in the region. After using this model to simulate three scenarios for the study area in 2035, namely inertial development, cultivated land protection, and ecological priority, it was found that the ecological priority scenario is the best mode for optimizing land use structure and promoting further growth in ecosystem service value in the Lixiahe area. [Conclusion] Emphasis should be placed on the protection of cultivated land resources, intensive utilization of existing construction land, strengthening the management of river and lake waters, and wetland restoration, to promote sustainable green development in the Lixiahe area in Jiangsu Province.